School resource center and students’ civilization in digital age / Shamila Mohamed Shuhidan ... [et al.] - Shuhidan, Shamila Mohamed; Abdul Majid, Mayasari; Shuhidan, Shuhaida Mohamed; Anwar, Norizan; Abd Hakim, Azma Asnawishah (Universiti Teknologi MARA, 2020)
In the 21st century, the School Resource Centre (SRC) is essential as an innovative educational practice that supports teaching-learning in the digital age. Previous studies have highlighted the beneficial roles of an SRC in terms of collections, SRC programs, and the provision of a conducive learning environment to school communities. However, due to the meaningful impact of technology, SRCs need to transform their traditional roles to more modern roles in the digital age in order to bring knowledge that is alive, interesting and relevant to meet users’ needs and demands, especially the millennials. The millennial generation is comprised of digital immigrants who are very competent in using technology devices but still lack information literacy skills and are marked by uncertainty because they face information overload due to the high dependency on the Internet and inability to solve real-life problems. In this study, the millennial generation was narrowed to secondary students aged between 13-17 years old. This paper aims to determine the type of activities held in SRCs that give impact on students’ civilization and support them in developing life-long learning habits which will enable them to be knowledgeable and responsible citizens in a civilized society. A survey was distributed to secondary students, and findings show that there is a positive indication with a 4.21 mean value (with Likert scale ranging between 1 to 5) on civilization for the use of SRCs. Education itself is evolving through changes in the curricula and use of enhanced technology which have changed the way students access information and interact with others in the civilized society. It is hoped that other than becoming information literate and knowledgeable persons, students can also show evidence of moral and intellectual advancement by being humane, ethical and reasonable as well as have the capabilities of leading an improved life and social wellbeing.